FORMATION AND DEVELOPMENT OF THE PRODUCTION MECHANISM OF FLOUR AND GRAIN ENTERPRISES ON THE BASIS OF THE CLUSTER SYSTEM - Alieva Janat Askarovna (Scholar Express Journals, 2022)
This article examines the formation and development of the production mechanism of flour and grain enterprises based on the cluster system
Keywords: Agar farmer and clusters, energy-saving flour; cluster and farmer; O’zdonmahsulot